Electrochemical measurement of the electronic structure of graphene via quantum mechanical rate spectroscopy - Lopes, Laís Cristine [UNESP]; Pinzón, Edgar Fabian [UNESP]; Dias-da-Silva, Gabriela [UNESP]; Feliciano, Gustavo Troiano [UNESP]; Bueno, Paulo Roberto [UNESP] (Elsevier, 2024)
Quantum-rate theory defines a quantum mechanical rate ν that complies with the Planck–Einstein relationship E=hν, where ν=e2/hCq is a frequency associated with the quantum capacitance Cq, and E=e2/Cq is the energy associated with ν. Previously, this definition of ν was successfully employed to define a quantum mechanical meaning for the electron-transfer (ET) rate constant of redox reactions, wherein faradaic electric currents involved with ET reactions were demonstrated to be governed by relativistic quantum electrodynamics at room temperature (Bueno, 2023c). This study demonstrated that the definition of ν entails the relativistic quantum electrodynamics phenomena intrinsically related to the perturbation of the density-of-states dn/dE=Cq/e2 by an external harmonic oscillatory potential energy variation. On this basis, the electronic structure of graphene embedded in an electrolyte environment was computed. The electronic structure measured using quantum-rate spectroscopy (QRS) is in good agreement with that measured through angle-resolved photo-emission spectroscopy (ARPES) or calculated via computational density-functional theory (DFT) methods. Electrochemical QRS has evident experimental advantages over ARPES. For instance, QRS enables obtaining the electronic structure of graphene at room temperature and in an electrolyte environment, whereas ARPES requires low temperature and ultrahigh-vacuum conditions. Furthermore, QRS can operate in-situ using a hand-held, inexpensive piece of equipment, whereas ARPES necessarily requires expensive and cumbersome apparatus.
Keywords: Conductance quantum; Density-functional theory; Density-of-state; Electronic structure; Graphene; Quantum capacitance; Quantum-rate spectroscopy; Quantum-rate theory